Encyclopedia of addictions - Hollen, Kathryn H. (Gale virtual reference library, 2009)
Contains frank and factual information about symptoms, causes, effects, prevention, and treatment of substance abuse (alcohol, nicotine, and drugs) and of behavioral addictions such as eating disorders, pathological gambling, and compulsive sexual activity.